Math, asked by kashishbariyekar, 11 months ago

simplify the expressions (5-3√3)^2

Answers

Answered by aryan073
1

Step-by-step explanation:

<svg width="35" height="35" viewBox="0 0 100 100">\ \textless \ br /\ \textgreater \ \ \textless \ br /\ \textgreater \ <path fill="Black" d="M92.71,7.27L92.71,7.27c-9.71-9.69-25.46-9.69-35.18,0L50,14.79l-7.54-7.52C32.75-2.42,17-2.42,7.29,7.27v0 c-9.71,9.69-9.71,25.41,0,35.1L50,85l42.71-42.63C102.43,32.68,102.43,16.96,92.71,7.27z"></path>\ \textless \ br /\ \textgreater \ \ \textless \ br /\ \textgreater \ <animateTransform \ \textless \ br /\ \textgreater \ attributeName="transform" \ \textless \ br /\ \textgreater \ type="scale" \ \textless \ br /\ \textgreater \ values="1; 1.5; 1.25; 1.5; 1.5; 1;" \ \textless \ br /\ \textgreater \ dur="2s" \ \textless \ br /\ \textgreater \ repeatCount="4000"> \ \textless \ br /\ \textgreater \ </animateTransform>\ \textless \ br /\ \textgreater \ \ \textless \ br /\ \textgreater \ </svg>

By using properties:

(5-3root3)²

=

( {5  - 3\sqrt{3} }^{2} )

 = 25 + 27 - 30 \sqrt{3}

52 - 30 \sqrt{3}

is the answer of this question OK

Answered by chocolateboy80
0

Answer:

52-30√3

Step-by-step explanation:

it is based on (a-b)^2

(5-3√3)^2

=25+27-30√3

=52-30√3

more further we can write like..2(26-15√3).....Ans.

Similar questions